2008
DOI: 10.2500/ajr.2008.22.3218
|View full text |Cite
|
Sign up to set email alerts
|

No Packing versus Packing after Endoscopic Sinus Surgery: Pursuit of Patients’ Comfort after Surgery

Abstract: Nasal packing can be safely used less frequently to help the patients experience less discomfort after ESS. The need for nasal packing after ESS can be decided by judicious estimation of bleeding during and after the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 14 publications
(25 reference statements)
0
48
0
1
Order By: Relevance
“…Their results showed that in unilateral endoscopic sinus surgery (ESS) cases, subjective estimated blood loss and mucosal inflammation were decreased in the no‐packing group. However, for bilateral ESS, no statistically significant clinical differences were found . Despite the lack of clear, compelling evidence to support the use of nasal packing, Nasopore (Stryker Corporation, Kalamazoo, MI) has become one of the most commonly used absorbable synthetic nasal‐packing materials in patients post‐ESS.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that in unilateral endoscopic sinus surgery (ESS) cases, subjective estimated blood loss and mucosal inflammation were decreased in the no‐packing group. However, for bilateral ESS, no statistically significant clinical differences were found . Despite the lack of clear, compelling evidence to support the use of nasal packing, Nasopore (Stryker Corporation, Kalamazoo, MI) has become one of the most commonly used absorbable synthetic nasal‐packing materials in patients post‐ESS.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of consensus for the end point of these studies appears to be a matter of discussion. A great number of the studies evaluated the outcomes from 1 to 12 weeks . There is only one study in addition to ours that compared packing until 6 months .…”
Section: Discussionmentioning
confidence: 99%
“…The most common approaches are the placement of a Merocel spacer in the middle meatus, or nothing at all. Studies have shown that nasal packing is uncomfortable for the patient and contributes to nasal obstruction and postnasal drip [53,54]. The senior author's preference is to place a Merocel middle meatal spacer upon completion of surgery, and to remove it within 24 h. The use of resorbable packing or gels has become quite popular.…”
Section: Packings and Dressingsmentioning
confidence: 98%